1996
DOI: 10.1051/apido:19960301
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and alloenzymatic characterisation in the Albanian honeybee population Apis mellifera L

Abstract: honeybee / Apis mellifera carnica / Apis mellifera macedonica / Apis mellifera ligustica / Albania / honeybee population / morphometric characterisation / alloenzymatic characterisation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
0
5
1
Order By: Relevance
“…The usefulness of the MDH-1 * and EST-3 * loci, as reported by Sheppard and Smith (2000), is strengthened by our data (three alleles for MDH-1 * and two alleles for EST-3 * ). In a related study made by Dedej et al (1996) for A. m. macedonica, two MDH-1 * alleles (MDH-1 * 100 and MDH-1 * 65) were noted but no polymorphisms for the EST-3 * and ME * loci were detected, observations not in accordance with our data. A study by Badino et al (1988) on honey bee populations from Greece, using 15 enzymic loci, found genetic polymorphisms only for MDH-1 * and EST-3 * .…”
Section: Discussioncontrasting
confidence: 75%
“…The usefulness of the MDH-1 * and EST-3 * loci, as reported by Sheppard and Smith (2000), is strengthened by our data (three alleles for MDH-1 * and two alleles for EST-3 * ). In a related study made by Dedej et al (1996) for A. m. macedonica, two MDH-1 * alleles (MDH-1 * 100 and MDH-1 * 65) were noted but no polymorphisms for the EST-3 * and ME * loci were detected, observations not in accordance with our data. A study by Badino et al (1988) on honey bee populations from Greece, using 15 enzymic loci, found genetic polymorphisms only for MDH-1 * and EST-3 * .…”
Section: Discussioncontrasting
confidence: 75%
“…Areas of hybridization have been detected in Choney bee populations: in Albania between A. m. carnica and A. m. macedonica (Dedej et al 1996); in FYROM by the interaction of native A. m. macedonica with A. m. ligustica and A. m. carnica , due to the traditional and longterm intensive importation of A. m. carnica and uncontrolled importation of A. m. ligustica queens (Uzunov et al 2009); in Bulgaria, where A. m. ligustica , A. m. carnica , and A. m. caucasica have commonly been reared for more than three decades, and strongly hybridized with the native A. m. macedonica (Ivanova et al 2007); in central Greece, commercial queen breeding and migratory beekeeping have contributed to the almost complete hybridization (Bouga et al 2005) of the four native subspecies originally described by Ruttner (1988). In addition, mitochondrial haplotypes characteristic of A. m. ligustica were detected in the Carniolan honey bee populations from Slovenia (Sušnik et al 2004), Croatia (Muñoz et al 2009), and Serbia (see Figure 1 in Nedić et al 2014 for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…Honeybees from France (Cornuet et al, 1982(Cornuet et al, , 1986, Italy (Badino et al, 1983;Sheppard and Berlocher, 1985;Comparini and Biasolo, 1991), Sicily (Badino et al, 1985), Norway (Sheppard and Berlocher, 1984), Turkey (Kandemir and Kence, 1995;Kandemir et al, 2000Kandemir et al, , 2005, Spain (Smith and Glenn, 1995;Arias et al, 2006), Albania (Dedej et al, 1996), Greece (Badino et al, 1988;Bouga et al, 2005a) and Bulgaria (Ivanova et al, 2007) have been analysed with this methodology. The allozymic information depicted from the Old World subspecies has been used to study gene flow between European-derived and African-derived honeybee populations in the New World, as 278 P. De la Rúa et al reviewed in Sheppard and Smith (2000;see also Schneider et al, 2004).…”
Section: Box 3 Nuclear Dna Analysismentioning
confidence: 99%